PENGARUH STADTERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN KELAS V SDN 28 PONTIANAK KOTA - Sundari, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis study aims to determine the effect of Student Teams Achievement Division Applying to the Outcomes of Vocational Education C grade V of Pontianak City State Elementary School. The method used is experiment with Quasy Ek-sperimental Design with Non Equivalent Control Group Design research design. The population is all Class V students consisting of 2 classes with 78 students. The samples were 39 Control class and 39 experiment class. Data collection techniques used are measurement techniques and data collection tools used there is a written test in the form of multiple choice as much as 40 questions. The mean score of post-test of control class 59,87 and post-test of experiment class is 67,88. The result of t-test is obtained tcount 2,5071 and t table (Î± = 5% with dk 76) equal to 1,995, which means thitung> ttable, hence Ha accepted means signitive and Ho rejected. Based on the calculation of the effect size (ES) of 0.56 with the medium category in the range 0.2 <ES> 0.8, so it is concluded that there is influence of the Student Teams Achievement Division model to the learning outcomes of civic education education class V Elementary School 28 Pontianak City.Â Keywords: Influence, Student Teams Achievement Division, Learning Outcomes.